2018
DOI: 10.3389/fncel.2018.00161
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neurofilament Integrity and Neuronal Morphology in Different Models of Focal Cerebral Ischemia and Human Stroke Tissue

Abstract: As part of the neuronal cytoskeleton, neurofilaments are involved in maintaining cellular integrity. In the setting of ischemic stroke, the affection of the neurofilament network is considered to mediate the transition towards long-lasting tissue damage. Although peripheral levels of distinct neurofilament subunits are shown to correlate with the clinically observed severity of cerebral ischemia, neurofilaments have so far not been considered for neuroprotective approaches. Therefore, the present study systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 75 publications
(96 reference statements)
9
44
3
Order By: Relevance
“…NF immunoreactivity has previously been shown to increase in the ischemic brain following experimental ischemia in rats and mice and the postmortem human ischemic brain (24,25). In the present study, we also observed intense neurofilament staining in ischemic neurons and in the infarcted brain parenchyma in two postmortem ischemic stroke cases with >7-day-old parietal and 3-7-day-old temporal lobe infarcts (Figure 1).…”
Section: Nf-l Levels Are Significantly Increased In Ischemic Stroke Psupporting
confidence: 83%
See 2 more Smart Citations
“…NF immunoreactivity has previously been shown to increase in the ischemic brain following experimental ischemia in rats and mice and the postmortem human ischemic brain (24,25). In the present study, we also observed intense neurofilament staining in ischemic neurons and in the infarcted brain parenchyma in two postmortem ischemic stroke cases with >7-day-old parietal and 3-7-day-old temporal lobe infarcts (Figure 1).…”
Section: Nf-l Levels Are Significantly Increased In Ischemic Stroke Psupporting
confidence: 83%
“…In the present study, we observed increased NF immunoreactivity in the ischemia-affected area compared to normal-appearing tissue in a 3-7-day-old temporal lobe infarct and a >7-day-old right parietal lobe infarct. The increased NF immunoreactivity is possibly related to an increase in detectable NF degradation products in the ischemic core due to structural cytoskeletal alterations in neurons following ischemia (25). Previous studies on postmortem tissues from victims of stroke and other focal lesions using immunostaining with antibodies specific for phosphorylated NF-H have demonstrated that NF phosphorylation (normally confined to axons) occurs aberrantly in perikaria and dendrites of neurons with axons projecting to damaged brain areas (26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Quantitative analyses of the immunofluorescence signals from collagen IV and fibronectin were based on five brain sections from each mouse, while these sections were selected concerning the following criteria: first, an unequivocal ischemic affection as indicated by a regional change of the fluorescence signal typically located in the right-sided neocortex and subcortical areas as known from own earlier studies (e.g., Mages et al, 2018), and second, the absence of tissue damage that prevents immunofluorescence-based analyses in large parts of the ischemia-affected hemisphere. This selection process allowed the analysis of six mice with an ischemia duration of 4 h and five mice with an ischemia duration of 24 h. As prerequisite for the following quantification, in each of the selected brain sections, seven regions of interests (ROIs) were arranged on the ischemia-affected hemisphere including six neocortical ROIs covering the ischemic border zone with most evident changes of the collagen IV immunosignal between ROIs 3 and 4, and a further ROI (number 7) in the subcortex, i.e., the striatum.…”
Section: Microscopy Image Processing and Quantification Of Fluorescmentioning
confidence: 99%
“…NF is a neuronal cytoskeletal protein, an intermediate filament that provides structural support for axons, as well as regulating their diameter (Iwanaga et al, 1989). Decreased NF expression indicates adverse protein rearrangement arising prior to alterations in axonal cytoskeleton (Mages et al, 2018), and RV is reported with adverse neuronal activities (Ekong et al, 2020;Nduohosewo and Ekong, 2020), which may have resulted in decreased expression and population in the present study. The present result is in line with Ekong et al (2016b), who reported that RV cause decreased NF expression in the olfactory bulb.…”
Section: Discussionmentioning
confidence: 54%